The multiple facets of the Golgi reassembly stacking proteins. - Vinke, F.P.; Grieve, A.G.; Rabouille, C. (The Biochemical Journal, 2011)
The mammalian GRASPs (Golgi reassembly stacking proteins) GRASP65 and GRASP55 were first discovered more than a decade ago as factors involved in the stacking of Golgi cisternae. Since then, orthologues have been identified in many different organisms and GRASPs have been assigned new roles that may seem disconnected. In vitro, GRASPs have been shown to have the biochemical properties of Golgi stacking factors, but the jury is still out as to whether they act as such in vivo. In mammalian cells, GRASP65 and GRASP55 are required for formation of the Golgi ribbon, a structure which is fragmented in mitosis owing to the phosphorylation of a number of serine and threonine residues situated in its C-terminus. Golgi ribbon unlinking is in turn shown to be part of a mitotic checkpoint. GRASP65 also seems to be the key target of signalling events leading to re-orientation of the Golgi during cell migration and its breakdown during apoptosis. Interestingly, the Golgi ribbon is not a feature of lower eukaryotes, yet a GRASP homologue is present in the genome of Encephalitozoon cuniculi, suggesting they have other roles. GRASPs have no identified function in bulk anterograde protein transport along the secretory pathway, but some cargo-specific trafficking roles for GRASPs have been discovered. Furthermore, GRASP orthologues have recently been shown to mediate the unconventional secretion of the cytoplasmic proteins AcbA/Acb1, in both Dictyostelium discoideum and yeast, and the Golgi bypass of a number of transmembrane proteins during Drosophila development. In the present paper, we review the multiple roles of GRASPs.